Clonidine exposures in children under 6 (2004–2017): a retrospective study. Issue 3 (19th March 2019) - Cairns, Rose; Brown, Jared A; Buckley, Nicholas A
Abstract : Objective: To describe trends in clonidine exposures in children under 6. Clonidine has become increasingly popular for management of paediatric behavioural disorders. Clonidine has a narrow therapeutic index, and toxicity can occur with inadvertent double dosing. Clonidine is not recommended for use in children under 6 years. Design and setting: A retrospective review of clonidine exposures in children under 6 reported to the New South Wales Poisons Information Centre (NSWPIC, Australia's largest poison centre), 2004–2017. This was compared with community clonidine utilisation using dispensing data from Australian Statistics on Medicines, 2004–2015. Australian trends were compared with clonidine exposure calls to US poison centres, 2006–2016. Main outcome measures: Trends in poisonings and dispensing; demographics, dose, exposure type, clonidine source, symptoms, disposition. Results: There were 802 clonidine exposures in the NSWPIC database, increasing 4.9% per year, 2004–2017 (95% CI 3.1% to 6.7%, p<0.001), correlated with increased dispensing, r=0.846 (95% CI 0.529 to 0.956, p<0.001). 78.6% were hospitalised and medical toxicologists were consulted in 7.2%, indicating high risk and/or morbidity. Clonidine was prescribed for the patient in at least 27.8%, providing evidence for prescribing outside of recommendations. US data reveals 19 056 clonidine exposures, with 3.7% increase per year, 2006–2016 (95% CI 2.2% to 5.3%, p<0.001). Conclusions: Clonidine exposures in children under 6 are increasing, and this trend is not isolated to Australia. Exposures have a high hospital referral rate and high morbidity. Caution should be exercised when prescribing clonidine, and parent/carer education is important for safe storage and increased vigilance when dosing.